Grado de microfiltración in vitro de ionómero vítreo y resina compuesta nanoparticulados en restauración de dientes primarios - Rojas Padilla, Sandra Vannesa (2013)
The purpose of this study was to compare the degree of in vitro microleakage of a glass ionomer (Ketac N100) and a composite resin (Z350 XT) nanoparticulate in primary teeth restorations. An experimental in vitro study was conducted, evaluating a total of 60 deciduous teeth, which were divided into two groups of 30 pieces. Standardized cavities were made on the labial surface, to be restored with the indicated materials, and then subjected to thermocycling and immersion in methylene blue to observe the degree of microfiltration with the Miller index. Comparing the degree of microleakage in vitro of both materials, it is concluded that the glass ionomer nanoparticulate showed the lowest degree of microfiltration (33.3 % had Grade 1) while the composite resin nanoparticulate had a higher degree of microleakage (76.7 % had Grade 3) with a highly significant statistical difference between the two groups evaluated (p < 0.01).